Photo-Voice as an Innovative Methodology in Higher Education: A Systematic Review - Muñoz Rodríguez, Darllyn Ismey; Carmona Rodríguez, Carmen; Bell Sebastián, Julián (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The adaptation to the EHEA has demanded the emergence of active methodologies attached to education, which are a key photovoice at different educational levels. However, research in the educational context, and specifically in Higher Education, is scarce. Therefore, the aim of this paper is to analyse the use of photovoice in higher education, through a systematic review based on the PRISMA 2020 Statement in three databases. Fifteen of the 408 studies identified met the inclusion criteria. The results position photovoice as an educational alternative with potential in Higher Education settings.